Speech in the Wayúu Culture (2017)
The main manifestations of culture, such as: myths, tales, chants, wisdom and values are all expressed through language. The wayúu culture has its own system of norms that is applied by a single character, named pütchipü’üi. This character, whose origins are found in the mythical world of the wayúu culture, is responsible for the proper and reliable use of words in his society; a symbol of perlocutionary nature for the wayúu, especially when dealing with conflictive situations. The means in which the word is materialized is the wayúunaiki language, a fully alive linguistic system. Our purpose is to highlight this particular aspect of the wayúu culture, which is usually ignored in the national scope of linguistic studies. We also wish to demonstrate that the word is a key pillar in the normative system of the wayúu.